Principles of environmental toxicology - Shaw, Ian (Taylor & Francis, 1999)
Historical review of human impact on the environment.--Effects of pollutants on ecosystems.--Environmental toxicity testing.--Environmental monitoring.--Human toxicology.--Fate and behaviour of chemicals in the environmental.--Radioactivity and the environment.--Legislation.--Prologue to the future.